Independent predictors of depressive symptoms and social isolation on 2-year all-cause mortality among the Korean elderly in a population-based cohort study: gender differences - Hyunsuk Jeong; Hyeon Woo Yim; Beom-Woo Nam (Epidemiology and Health, 2022)
OBJECTIVES This study examined whether depressive symptoms and social isolation were independent predictors of 2-year all-cause mortality among the elderly using data from a population-based cohort study. METHODS In total, 1,033 participants (320 men and 713 women) older than 60 years of age participated in this study. Depressive symptoms, social isolation status, and socio-demographic and health-related covariates were assessed at baseline. The primary outcome measure was 2-year all-cause mortality. Data were collected through in-person interviews by trained interviewers. The GENMOD procedure was used to calculate relative risks (RRs). RESULTS Of the 1,033 participants, 102 (40 men and 62 women) died within the follow-up period of 2 years. During the 2-year follow-up period, 17.8% of depressed men and 12.3% of depressed women died, and 29.8% of socially isolated men and 14.9% of socially isolated women died. Social isolation was an independent predictor of mortality in elderly men (adjusted relative risk [aRR], 4.6, 95% confidence interval [CI], 2.0 to 10.2), while depressive symptoms were an independent predictor of mortality in elderly women (aRR, 2.0; 95% CI, 1.2 to 3.6) when controlling for potential confounding factors. However, the depressive symptoms detected using the geriatric depression scale were not associated with mortality in men, and social isolation was not associated with mortality in women. CONCLUSIONS The effects of depressive symptoms and social isolation on 2-year all-cause mortality within an elderly population differed according to gender. Gender-specific community-based interventions must be developed to potentially reduce 2-year all-cause mortality among the elderly.